Penampang Anatomi dan Pertumbuhan Apokol Tanaman Aren di Kecamatan Pulau Punjung Kabupaten Dharmasraya (Arenga pinnata L) - Suhendra, Dede; Wisnubroto, Muhammad Parikesit; Rahman, Muhammad Aulia (UNIVERSITAS LABUHANBATU, 2024)
The sugar palm plant is a potential plant because almost all parts of the sugar palm tree are useful and can be used for various needs,starting from the roots,stems,leaves, fibers and its products (nira, starch or flour, and fruit)the main product of the sugar palm plant is nira which is processed into various products, such as sugar,alcohol,and biofuel.Sugar palm plants generally live in tropical environments).Sugar palm is a type of palm plant that has a very wide distribution in Indonesia, with an area of 62,009 ha, consisting of Sumatra with an area of 15,802 ha, Java 19,757 ha, Bali 587 ha, NTB 1,816 ha, Kalimantan5,401 ha, Sulawesi16,951 ha and Maluku 1,696 ha. Sugar palm seeds consist of seed coat (testa), endosperm, and embryo, and the embryo becomes a food reserve for apokol. Apokol is a white coral tissue where shoots and roots grow, appearing 2-4 weeks after planting.The development of the potential of sugar palm has problems related to the availability of sugar palm seeds which are currently still hampered because the nature of sugar palm seeds is waterproof so that it will inhibit the ability of the seeds to germinate. The growth process of sugar palm beginswith the emergenceapokol after that shoots will appear in the germinations. But no ideal apokol was found thatlong in determining the process of shoot growth. This study was conducted where the results of the data on apokol diameter, apokol length, root length and number of roots were obtained. Keywords : apocol, anatomy, bud